Reading the dyslexic brain: multiple dysfunctional routes revealed by a new meta-analysis of PET and fMRI activation studies - Paulesu, Eraldo; Danelli, Laura; Berlingeri, Manuela (Frontiers in Human Neuroscience, 2014)
Developmental dyslexia has been the focus of much functional anatomical research. The main trust of this work is that typical developmental dyslexics have a dysfunction of the phonological and orthography to phonology conversion systems, in which the left occipito-temporal cortex has a crucial role. It remains to be seen whether there is a systematic co-occurrence of dysfunctional patterns of different functional systems perhaps converging on the same brain regions associated with the reading deficit. Such evidence would be relevant for theories like, for example, the magnocellular/attentional or the motor/cerebellar ones, which postulate a more basic and anatomically distributed disorder in dyslexia. We addressed this issue with a meta-analysis of all the imaging literature published until September 2013 using a combination of hierarchical clustering and activation likelihood estimates. The clustering analysis on 2360 peaks identified 193 clusters, 92 of which proved significant for spatial extent. Following binomial tests on the clusters, we found left hemispheric network specific for normal controls (i.d. of reduced involvement in dyslexics) involving the left inferior frontal, premotor, supramarginal cortices and the left infero-temporal and fusiform region: these were specific for reading and the visual-to-phonology processes. There was also a more dorsal left fronto-parietal network: these clusters included peaks from tasks involving phonological manipulation, but also motoric or visuo-spatial perception/attention. No cluster was identified in area V5 for no task, nor in cerebellar clusters either. We conclude that the available literature demonstrates a specific lack of activation of the left occipitotemporal cortex in dyslexics that is specific for reading and reading-like behaviours and for visuo-phonological tasks. Additional deficits may be associated with altered functionality of dorsal fronto-parietal cortex.